Sectarianism in The Yemeni Political Field - Al-Qabili, Nada (2020)
The rise of the Houthi movement was met with a parallel rise of sectarian discourses and attitudes particularly in the aftermath of the 2011 uprising. However, these dynamics can be traced to earlier forces and reconfigurations that have shaped the Yemeni political field over the longue durée. By employing a Bourdieusian framework to study the rise of sectarian discourses and attitudes, this thesis seeks to explain the interplay within and between local and regional factors to understand the strategic employment of sectarianism, not only by Yemen’s political elite, but also by Ansarullah. In so doing, this works details how the Salih regime and the Houthi leadership employed sectarian discourse as a form of symbolic capital in the competition to dominate the Yemeni political field. The thesis builds on Pierre Bourdieu’s concepts of symbolic capital/power, the political field, and the habitus to provide a more holistic understanding of the Houthi movement and the rise of sectarianism in Yemen. Moreover, instead of portraying Ansarullah as a mere proxy that has been caught amidst a rivalry of two greater regional hegemonies, this work aims to bring forward a local perspective by engaging with concepts and ideas which the Houthis have used to define and construct their identity and movement.